PSIKOLOGI PENDIDIKAN DI ERA DIGITAL: TANTANGAN KOGNITIF DAN EMOSIONAL PESERTA DIDIK DI SMA INTEGRAL HIDAYATULLAH BATAM - Kamarul Zaman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the cognitive and emotional challenges experienced by students in digital era learning from an educational psychology perspective within the context of an Islamic secondary school. The rapid integration of digital technology into education has significantly influenced how students maintain attention, process information, and regulate emotions under increasing academic demands. This research employed a qualitative approach using a case study design. Data were collected through in depth interviews, classroom observations of digital-based learning, and document analysis, and were analyzed thematically through data reduction, data display, and conclusion drawing.The findings indicate that students face substantial cognitive challenges, including reduced learning focus, digital distractions, and increased cognitive load due to media multitasking. In addition, emotional challenges emerged in the form of academic stress, performance anxiety, mental fatigue, and fluctuating learning motivation. These results highlight the crucial role of teachers as learning facilitators and psychological guides, as well as the role of schools as regulatory and supportive environments in managing digital technology use. The study underscores the importance of low-distraction instructional design, emotional regulation support, and the integration of Islamic values to promote students’ psychological well-being and learning quality in the digital era.